Müntzer, Taubes, and the Anabaptists: Emancipatory History and Political Theology - Kennel, Maxwell ca. 20./21. Jahrhundert (Political theology, 2019)
The radical apocalypticism of the sixteenth century mystic and revolutionary Thomas Müntzer has served as an enduring resource for the political left, from early investigations by Engels and Bloch to the recent works of Alberto Toscano and Wu Ming. In one of his lesser-studied works - the 1947 dissertation Occidental Eschatology - Jewish philosopher Jacob Taubes places Müntzer at a key juncture in the history of eschatology, first by situating him at the end of the Reformation period, and then by connecting his revolutionary apocalypticism to the critiques of Hegel leveled by Marx and Kierkegaard. This study aims to give a new perspective on Taubes as a philosopher of history, first by showing potentially surprising connections between Taubes' Occidental Eschatology and the historiography of Anabaptism, and second by making suggestions about how Taubes' distinctively emancipatory philosophy of history might contribute to thinking about time and history within contemporary political theology.